Mood states and motor performance: a study with high performance voleybol athletes - João Nickenig Vissoci; José Luiz Lopes Vieira; Saulo Luders Fernandes; Lenamar Fiorese Vieira (Universidade Federal de Santa Catarina, 2008)
The objective of this research was to investigate the relationship between the sporting performance and mood states of high performance volleyball athletes. Twenty-three adult athletes of both sexes were assessed. The measurement instrument adopted was the POMS questionnaire.1 Data collection was carried out individually during the state championships. Dada were analyzed using descriptive statistics; the Friedman test for analysis of variance and the Mann-Whitney test for differences between means. The results demonstrated that both teams exhibited the mood state profi le corresponding to the "iceberg" profi le. In the male team, vigor remained constant throughout all phases of the competition, while in the female team this element was unstable. The male team's fatigue began low, during the training phase, with rates that rose as the competition progressed, with statistically significant differences between the first and last matches the team played. In the female team, the confusion factor, which was at a high level during training, reduced progressively throughout the competition, with a difference that was significant to p ≤ 0.05. With relation to performance and mood profile, the female team exhibited statistically significant differences between the mean vigor and fatigue factors of high and low performance athletes. It is therefore concluded that the mood state profi le is a factor that impacts on the motor performance of these high performance teams. Resumo Esta pesquisa teve por objetivo investigar a relação entre desempenho esportivo e o estado de humor de atletas de voleibol de alto rendimento. Foram avaliados 23 sujeitos de ambos os sexos da categoria adulta. O instrumento de medida utilizado foi o questionário POMS1. A coleta dos dados foi realizada de forma individual, durante o campeonato estadual. Para análise dos dados, utilizou-se a estatística descritiva, o teste de Friedman para análise de variância e o de Mann-Whitney para diferença de médias. Os resultados evidenciaram que ambas as equipes apresentaram o perfil de estado de humor correspondente ao perfil iceberg. Na equipe masculina, o vigor permaneceu constante durante todas as fases da competição, enquanto na feminina esse fator mostrou-se instável; o fator fadiga, na equipe masculina, apresentou, na fase de treino, índices baixos, que aumentaram com o progresso da competição, mostrando diferenças estatisticamente significativas entre o primeiro e o último jogo da equipe; na equipe feminina o fator confusão, que na fase de treino teve índice alto, baixou progressivamente durante a competição, apresentando diferença significativa para p ≤ 0.05. Em relação ao desempenho e ao perfil de estado de humor, a equipe feminina apresentou diferenças estatisticamente significativas entre os valores médios nos fatores vigor e fadiga para os atletas de baixo e médio desempenho. Assim, conclui-se que o perfil de estado de humor se apresentou como um fator interveniente no desempenho motor destas equipes de alto rendimento.